Factors improving childbearing intention among young adults in the context of low birth rate in China: ISM approach - Xu, Yuanyuan; Jamiah Manap,; Siti Fardaniah Abdul Aziz,; Yao, Shuying; Liu, Haibao (Penerbit Universiti Kebangsaan Malaysia, 2025)
In the context of China’s low fertility rate, critical success factors (CSFs) to enhance young adults’ childbearing intentions are considered an important means to achieve sustainable population development in China. The aim of this paper is to propose a methodology to identify critical success factors (CSFs) for enhancing young adult’s childbearing intentions in China. A total of 21 critical success factors (CSFs) were identified through a literature review and input from academic and industry practitioners. This paper adopts an Interpretative Structural Modeling (ISM) approach to establish the interrelationships among these factors, which not only helps to understand the relative relationships among the critical success factors, but also identifies their interdependencies in practical applications. In addition, the importance of the factors in enhancing childbearing intentions was identified through analysis based on their drivers and dependencies. It was found that improvement of fertility perception is the direct influential factor that motivates young adults to increase their childbearing intentions. This paper demonstrates the application of the proposed model in practice, using Chinese young adults as an example. The study can help academics, government regulators and practitioners to emphasize the implementation of measures to increase childbearing intentions.